Growth performance of a neonate exclusively fed on buffalo milk: a case study - Khattak, Muhammad Muzaffar Ali Khan (Asian Network for Scientific Information, 2003)
A full term baby born through C-section with a birth-weight of 7.7lbs, which were within the standard range of 5.5-7.7 lbs. The baby was kept on the Nestle`s Lactogen-1 with the advice of a classified Pediatrician when the mother was failed to breast-feed the baby. Due to complications in the weight-gain with the Nestle`s Lactogen-1, it was abandoned at the age of fourth month and fresh boiled buffalo milk was introduced. The protein requirements were adjusted according to the recommended level of 2.46 g/kg body weight by adding boiled water. The protein contents of the buffalo milk were assumed to be 4-gram/100 ml of fresh milk. The amount of water lost during the boiling of the fresh milk was adjusted to the original volume of the milk. The milk was fed at ad labitum to the baby; however, the volume consumed over the reported period was not recorded. At the end of sixth month banana was introduced to the baby and at the start of ninth month family food was gradually introduced. The body weight was regularly recorded weekly and on monthly basis with the pediatric scale. In this case study it was noticed that when the infant was on the Nestle`s Lactogen-1, the weight-gain was severely less during first four months. However, the weight-gain with buffalo milk was steady up to 24 months. This study shows that the buffalo milk is as good as other milk sources provided that its protein content is adjusted properly.